EVALUATION OF SKILL BASED ACTIVITIES FOR LANGUAGE LEARNERS IN PTB TEXT BOOK AT MATRICULATION LEVEL - Lubna Shahzadi; Hafiz Muhammad Hammad Javed; Sajid Ali; Sadaf Saleh; Rukhsana Tabasum (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study is designed to evaluate English textbook 10th grade level prescribed by Punjab textbook board Lahore, Pakistan. The main objective of this study is to evaluate the activities present in textbook to contribute that the textbook is suitable for the improvement of English language learners in Pakistani scenario. Researcher used mixed method of research. Data was collected and analyzed by researcher qualitatively and quantitatively. Collected data was analyzed by applying SPSS software by researcher. Descriptive statistical method is used to evaluate the textbook and activities present in textbook. The researcher applied self-constructed checklist to gain the objectives of study. The analytical data and results related textbook evaluation is shown in the form of tables and graphs. The analysis of data shows that textbook is not fulfilling the requirement of Pakistani students properly. The division of activities, regarding four basic skills of language learning is not equally distributed in textbook. It is concluded that division of activities is not equal and appropriate and it is problematic area which needs serious consideration.